2010
DOI: 10.1002/biot.201000199
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoglycerate mutase knock‐out mutant Saccharomyces cerevisiae: Physiological investigation and transcriptome analysis

Abstract: The yeast Saccharomyces cerevisiae is able to adapt its metabolism to grow on different carbon sources and to shift to non‐fermentative growth on C2 or C3 carbon sources (ethanol, acetate, or glycerol) through the activation of gluconeogenesis. Here, we studied the response to the deletion of the glycolytic and gluconeogenic gene GPM1, encoding for phosphoglycerate mutase. It was previously shown that a S. cerevisiae strain with non‐functional copies of GPM1 can only grow when glycerol and ethanol are both pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 57 publications
2
9
0
Order By: Relevance
“…1). We confirmed the data of Papini et al [38] and showed that, similar to glucose, galactose inhibits the growth of Δgpm1 cells (Fig. 2).…”
supporting
confidence: 92%
See 1 more Smart Citation
“…1). We confirmed the data of Papini et al [38] and showed that, similar to glucose, galactose inhibits the growth of Δgpm1 cells (Fig. 2).…”
supporting
confidence: 92%
“…The Δgpm1 strain can grow in the presence of a mixture of glycerol and acetate (or ethanol) as carbon sources. In this case acetate (or ethanol) is metabolized downstream of phosphoglycerate mutase and produces substrates for the Krebs cycle, while glycerol is consumed by the enzymes upstream of phos phoglycerate mutase and serves as a substrate for gluco neogenesis [38]. It was shown that addition of glucose inhibits growth of Δgpm1 cells [39].…”
mentioning
confidence: 99%
“…4). These data agree with the data of Papini and coworkers [24]. This work describes the effect of phosphoglycerate mutase dele tion on gene expression.…”
Section: Discussionsupporting
confidence: 92%
“…This work describes the effect of phosphoglycerate mutase dele tion on gene expression. In particular, they showed that the deletion stimulates the expression of many stress response genes [24]. Thus, the regulatory role of triosephosphates in yeast physiology requires further study.…”
Section: Discussionmentioning
confidence: 99%
“…A checkmark indicates that the reaction catalysed by the enzyme has a significant centrality in the corresponding species; a hyphen indicates not significant; n.a. indicates the corresponding enzyme is not annotated for the species.enzymeEC no.BSECSCCRATHSreferencescatalase1.11.1.6n.a.[34,35]superoxide dismutase1.15.1.1n.a.[36–38]carbonic anhydrase4.2.1.1n.a.[3945] l -arabinose isomerase5.3.1.4n.a.n.a.n.a.[46,47]phosphoglycerate mutase5.4.2.1[4851]…”
Section: Resultsmentioning
confidence: 99%